A glance on the role of actin in osteogenic and adipogenic differentiation of mesenchymal stem cells - Khan, Asmat Ullah (Stem Cell Res Ther, 2020)
Mesenchymal stem cells (MSCs) have the capacity to differentiate into multiple lineages including osteogenic and adipogenic lineages. An increasing number of studies have indicated that lineage commitment by MSCs is influenced by actin remodeling. Moreover, actin has roles in determining cell shape, nuclear shape, cell spreading, and cell stiffness, which eventually affect cell differentiation. Osteogenic differentiation is promoted in MSCs that exhibit a large spreading area, increased matrix stiffness, higher levels of actin polymerization, and higher density of stress fibers, whereas adipogenic differentiation is prevalent in MSCs with disrupted actin networks. In addition, the mechanical properties of F-actin empower cells to sense and transduce mechanical stimuli, which are also reported to influence differentiation. Various biomaterials, mechanical, and chemical interventions along with pathogen-induced actin alteration in the form of polymerization and depolymerization in MSC differentiation were studied recently. This review will cover the role of actin and its modifications through the use of different methods in inducing osteogenic and adipogenic differentiation.